IS Olympics: Information Systems in a Diverse World CAiSE Forum 2011, London, UK, June 20-24, 2011, Selected Extended Papers - Nurcan, Selmin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the proceedings of the CAiSE Forum from the 23rd International Conference on Advanced Information Systems Engineering (CAiSE 2011), held in London, UK, June 2011. The CAiSE 2011 Forum was a place to present and discuss new ideas, emerging topics, and controversial positions; and to demonstrate innovative tools and systems related to information systems engineering. The 15 papers presented in this volume were carefully reviewed and selected from 46 submissions. The reworked and extended versions of the original presentations cover topics such as business process management, enterprise architecture and modeling, model-driven development, and requirements engineering.
Keywords: Economics; Software engineering; Artificial intelligence; Information systems; Management information systems; Economics/Management Science; Business Information Systems; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl. Internet).; Software Engineering; Artificial Intelligence (incl. Robotics).